(untitled) (International Journal of Food and Nutritional Sciences, 2021)
In an era marked by the relentless evolution of wireless communication technologies, the demand for versatile and adaptable antennas has never been more pronounced. This paper delves into the realm of "On-Demand Frequency Reconfigurable Antennas," an innovative approach poised to redefine wireless communication paradigms in next-generation devices. With an emphasis on real-time adaptability, these antennas hold the promise of reshaping the way we experience connectivity in an increasingly dynamic wireless landscape. The paper commences with a thorough exploration of the prevailing wireless communication landscape, setting the stage for the imperative need for antennas capable of seamlessly adapting to the diverse demands of emerging standards and frequency bands. It presents an insightful literature review, charting the evolution of frequency reconfigurable antennas and underscoring the limitations of static, fixed-frequency counterparts in the face of dynamic wireless ecosystems.